Prototip Mursyid Thoriqoh dan Nilai-Nilai Bimbingan Konseling Berkearifan Lokal: Studi Kasus Abuya Muhtadi Mursyid Thoriqoh Sadziliyah Pandeglang Banten - Ahmad Waki; Ikhsan Maulana (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research examines the prototype of Mursyid Thoriqoh and the values of guidance and counseling based on local wisdom through a case study of Abuya Muhtadi, a Mursyid Thoriqoh Sadziliyah in Pandeglang, Banten. Using a descriptive qualitative approach, this research aims to understand the spiritual relationship between murshids and students in the context of local-based spiritual counseling guidance. The research results reveal three main dimensions: (1) rituals and spiritual relationships as spiritual counseling practices that align students with their murshid through dhikr and rabitah activities; (2) a comparison between the spiritual counseling practices of the tarekat and humanistic concepts which show harmony between the function of the murshid as a guide and the student as a seeker of truth; and (3) the phenomenon of humanization in spiritual counseling, which emphasizes the importance of normativity and philosophy of the murshid-disciple relationship. This research shows that the spiritual values in thoriqoh contribute significantly to the practice of Islamic guidance counseling which is holistic and based on local wisdom.